The role of m6A regulators mRNA expression in peripheral blood mononuclear cells in chronic hepatitis B: a novel diagnostic and prognostic indicator - Xiu Han; Chengyu Xu; Yahui Song; Xiangwei Wu; Liting Zhou; Tianfeng Wu; Yiling Chen; Lin Wang; Qingzhen Han (BMC Gastroenterology)
Abstract Background Chronic hepatitis B (CHB) is a major health problem worldwide and is a major contributor to the progression of cirrhosis and hepatocellular carcinoma (HCC). Accurate monitoring of the immune response and liver inflammation in CHB patients is critical for effective disease management. N6-methyladenosine (m6A) plays a pivotal role in viral replication and immune modulation. However, the clinical significance of m6A regulators in the host immune system during CHB is still unclear. This study investigated the expression of key m6A regulators (METTL3, METTL14, IGF2BP3, and ALKBH5) in peripheral blood mononuclear cells (PBMCs) from CHB patients to explore their potential as noninvasive biomarkers for CHB diagnosis. Methods A total of 119 participants were recruited, among which 101 were CHB patients and 18 were healthy controls. PBMCs were isolated, and the mRNA expression levels of four key m6A regulators were analysed via quantitative real-time PCR (qRT‒PCR). Spearman correlation analysis was used to investigate the relationships between m6A regulator expression and inflammatory markers. Univariate and multivariate logistic regression analyses were performed to identify independent risk factors for CHB. Results The mRNA expression levels of METTL3 decreased in the LC, CHB (no-LC) (CHB without LC) and HC (healthy control) groups, and the differences were statistically significant (P < 0.05). METTL14 demonstrated a comparable expression pattern, although significant differences were evident only between the LC and HC groups (P < 0.05). ALKBH5 and IGF2BP3 levels were lower in LC patients than in CHB patients (non-LC patients) (P < 0.05). Moreover, METTL3 and METTL14 were negatively correlated with inflammation and cirrhosis markers, such as the neutrophil‒lymphocyte ratio (NLR) and the platelet‒lymphocyte ratio (PLR), but positively correlated with the lymphocyte‒monocyte ratio (LMR) (P < 0.05). Univariate analysis identified METTL3, PLR and AST as significant predictors of CHB. Multivariate logistic regression confirmed that reduced METTL3 expression, PLR and AST were independent risk factors for CHB progression (P < 0.05). Conclusion These findings suggest that m6A regulators, particularly METTL3, are associated with CHB progression and immune response modulation. METTL3, in combination with other inflammatory markers, is a promising non-invasive biomarker for monitoring CHB disease activity, providing new insights into HBV-related disease progression and potential therapeutic targets.